My Experience is Mine to Tell: Challenging the abolitionist victimhood framework - Cojocaru, Claudia (Anti-trafficking review, 2016)
This article is an analytical auto-ethnography of an art exhibit on trafficking into the sex industry in New York City in 2015. The analysis is informed by my own experience as a formerly trafficked person, and by other women’s own interpretations of their lived realities as trafficked or as migrant workers in the Japanese sex industry. This paper challenges the abolitionist movement’s unidimensional interpretation of all women engaged in sex work as victims trafficked in the sex industry; and introduces the concept of ‘secondary exploitation’, where these representations are framed and repackaged for consumption by opportunistic actors, while arguably further stigmatising and marginalising already vulnerable women